2019
DOI: 10.1007/s12250-019-00148-7
|View full text |Cite
|
Sign up to set email alerts
|

The DEAD-Box RNA Helicase DDX1 Interacts with the Viral Protein 3D and Inhibits Foot-and-Mouth Disease Virus Replication

Abstract: Foot-and-mouth disease virus (FMDV) can infect domestic and wild cloven-hoofed animals. The non-structural protein 3D plays an important role in FMDV replication and pathogenesis. However, the interaction partners of 3D, and the effects of those interactions on FMDV replication, remain incompletely elucidated. In the present study, using the yeast two-hybrid system, we identified a porcine cell protein, DEAD-box RNA helicase 1 (DDX1), which interacted with FMDV 3D. The DDX1-3D interaction was further confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…DDX1 is another stress granule resident protein [12] and has been found to inhibit or facilitate diverse viral infections including HIV, foot and mouth disease virus (FMDV), and transmissible gastroenteritis virus [18,71,75,76]. DDX1 was identified in a two-hybrid screen for HIV-Rev interactors and was shown to modulate the localization of Rev and the splicing of HIV mRNA.…”
Section: P-body and Stress Granule Helicases In Viral Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…DDX1 is another stress granule resident protein [12] and has been found to inhibit or facilitate diverse viral infections including HIV, foot and mouth disease virus (FMDV), and transmissible gastroenteritis virus [18,71,75,76]. DDX1 was identified in a two-hybrid screen for HIV-Rev interactors and was shown to modulate the localization of Rev and the splicing of HIV mRNA.…”
Section: P-body and Stress Granule Helicases In Viral Infectionmentioning
confidence: 99%
“…Moreover, in a yeast model of Tombus virus infection, Ded1 and Dbp2 enhance viral replication by unwinding 3 secondary structure to promote plus-strand RNA synthesis [82]. DDX1 inhibits foot and mouth disease virus and increases IFNβ production in infected cells [76]. DDX1 acts as a coactivator of NF-κB-mediated transcription via interaction with RelA, a function which requires intact helicase activity [19].…”
Section: P-body and Stress Granule Helicases In Viral Infectionmentioning
confidence: 99%
“…Another gene DDX1 on BTA11 was reported to be involved in bovine mammary involution in environmental stress conditions (Dado-Senn et al, 2018). DDX1 is also reported to be associated with linoleic acid content in Nellore cattle (Lemos et al, 2016) and viral resistance (Xue et al,2019).…”
Section: Discussionmentioning
confidence: 99%
“…Further study has indicated that 2C and Nmi induce a type I IFN response, and expression of FMDV 2C or Nmi significantly suppresses VSV replication ( Zheng et al, 2014 ). In addition, 3D pol interacts with DEAD-box RNA helicase 1 (DDX1), which has been identified to inhibit FMDV replication due to its ATPase or helicase activity and induce the production of host IFN-β protein to enhance antiviral innate immunity ( Xue et al, 2019 ). In addition, the non-coding regions (i.e., 5′ Grubman and Baxt, 2004 ).…”
Section: Fmdv Proteins Regulate Host Innate Immunitymentioning
confidence: 99%